GeoSystems today : an interactive casebook - Ford, Robert E. (John Wiley & Sons, 1999)
This book is contains a series of eight environmentally related case studies designed as a supplement for a college course in a topic such as environmental geology, earth systems science, physical geography, etc. The case studies are well done and are intimately linked to a web site which further elicidates each of the issues in an interactive manner. A major problem with this book is its extraordinary cost, which may outweigh its potential benefits if used in a college course along with an expensive core textbook and lab manual.